AN ASSESSMENT OF THE INFLUENCE OF MATHEMATICS TEACHERS' TRAINING ON USE OF QUESTIONING TECHNIQUE AND STUDENTS' ACHIEVEMENT IN MATHEMATICS IN PUBLIC SECONDARY SCHOOLS IN MWALA SUB-COUNTY, MACHAKOS COUNTY, KENYA - Mutisya, Muthusi Francis; Mulwa, David M.; Muola, James M. (Journal of Education and Practice, 2019)
Purpose: Mathematics' teachers play an important role in teaching of concepts in mathematics and ensuring that students register good grades in tests. However, in Mwala Sub-county, the scenario is different with many students registering low achievement in mathematics. Thus, the purpose of this study was to assess the influence of mathematics' teachers training on use of questioning technique on students' achievement in mathematics in public secondary schools in Mwala Sub-county, Machakos County, Kenya. Methodology: The study was guided by the learning theory. This study adopted mixed methodology and thus applied concurrent triangulation research design. Questionnaires were used to gather quantitative data from mathematics' teachers whereas interview guides were used to collect qualitative data from principals. Qualitative data were analyzed thematically based on study objectives and presented in narrative form. Quantitative data were analyzed using descriptive statistics and inferentially using linear regression analysis in Statistical Package for Social Sciences (SPSS Version 23) and presented using tables. Findings: The study established that many mathematics' teachers have basic training on how to use the questioning technique in teaching mathematics. However, this has not improved students' achievement in mathematics. Contribution to theory, policy and practice: The study recommends that mathematics' teachers should undergo many in-service trainings on how improve the questioning technique skills. Mathematics' teachers interact more with experienced colleagues by attending seminars and workshops designed to improve their experience and levels of exposure to different approaches of questioning. The Ministry of Education should create room for more in-service trainings for the newly recruited mathematics' teachers.